PENGARUH PENDIDIKAN KESEHATAN DENGAN MEDIA SOUND SLIDE TERHADAP PENGETAHUAN DAN TINDAKAN DALAM PEMILIHAN JAJAN PADA ANAK USIA SEKOLAH DASAR DI SDN GARANGAN - Laela Novianti; Titik Anggraeni; Hana Rosiana Ulfah; Sutanta Sutanta; Herbasuki Herbasuki; Farhan Nafis Sajidalloh (STIKES Estu Utomo, 2025)
Background: School Children's Snack Food (PJAS) is still an important problem. Lack of knowledge is one of the reasons why children continue to consume unhealthy snacks. Even though these snacks contain additives that are carcinogenic to the body. The results of monitoring by the POM Agency show that school children's snacks do not meet the requirements, ranging from 40% - 44%. School children's snacks do not meet food safety requirements due to the use of dangerous ingredients that are prohibited for use in food such as formaldehyde, borax, rhodamine B dye and methanyl yellow. This is certainly a serious problem that requires attention from all parties. Additives that accumulate in a child's body will cause dangerous diseases. One strategy to improve children's knowledge and attitudes is through health counseling or education. Objectives: This study aims to determine the effect of health education using sound slide media on knowledge and action in choosing snacks among elementary school age children at SDN Garangan. Method: This study aims to determine the effect of health education using sound slide media on knowledge and action in choosing snacks among elementary school age children at SDN Garangan. Result: The results of the bivariate analysis show that there is a significant influence between the influence of health education on knowledge and actions in choosing snacks, with a value of p=0.000 (p<0.05), which means that there is an influence of knowledge and actions before and after being given health education. Conclusion: There is an influence of health education using sound slide media on knowledge and action in choosing snacks for elementary school age children at SDN Garangan in 2024.